Clinical outcome of abdominal sacrocolpopexy in vault prolapse - Aparna Patil; Sheela HS; Madhva Prasad S; Samskruti Reddy (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: To describe the clinical outcome of patients undergoing abdominal sacrocolpopexy for posthysterectomy vault prolapse. Methods: This is a prospective observational study over a period of 2 years among patients who underwent the procedure. Demographic characteristics, POP-Q staging, intraoperative events, postoperative outcomes and complications were noted. Follow-up regarding outcome was done at 3 months, 6 months and 1 year. Results: 15 patients were studied with a mean age of 52 years and mean parity of 3. Most of the patients had stage 3 or 4 vault prolapse. Intraoperative complications were encountered in 3 patients (one bladder injury, one bowel injury and one excessive hemorrhage) which were managed appropriately. On short term follow up one patient had dyspareunia and one patient had urinary dysfunction. Long term follow-up showed one patient having chronic pelvic pain. None of the patients had recurrence of vault prolapse. Conclusion: Abdominal sacrocolpopexy is a safe and an effective procedure for vault prolapse.